Acoustic presence and vocal repertoire of bowhead whales (Balaena mysticetus) in eastern and central Fram Strait - Thomisch, Karolin; Hiemer, Katharina; Boebel, Olaf; Burkhardt, Elke; Spiesecke, Stefanie; Van Opzeeland, Ilse (Frontiers in Remote Sensing, 2022)
Bowhead whales (Balaena mysticetus) of the East Greenland-Svalbard-Barents Sea (Spitsbergen) population are still considered endangered, but knowledge on spatio-temporal distribution patterns and behavioral aspects remains scarce, yet crucial for this population’s conservation. Long-term passive acoustic recordings were collected at five locations in central and eastern Fram Strait (78-79°N, 0-7°E) as part of the Ocean Observing System FRAM (Frontiers in Arctic Marine Monitoring). Data recorded in 2012 and 2016/2017 were analyzed for the acoustic occurrence of bowhead whales at hourly resolution using a combination of automated and manual analyses. Bowhead whales were acoustically present from autumn throughout the winter months (October-February) and occasionally in spring (March-June), supporting hypotheses that Fram Strait is an important overwintering area. Acoustic presence peaked between mid-November and mid-December with bowhead whale calls recorded almost daily, often hourly for several consecutive days. The observed peak in acoustic presence coincided with the presumed mating period of bowhead whales, starting in late winter, indicating that Fram Strait may also serve as a mating area. Detailed analyses of recordings of a single year and location revealed eight distinct bowhead whale song types, comprising simple songs and call sequences. No bowhead whales were recorded in summer (July-September), indicating that they had migrated to summering areas or resided outside the detection range. Compared to previous studies in western Fram Strait, bowhead whale detections in our recordings were less frequent and recorded songs were less complex. The observed regional differences in bowhead whale acoustic behavior across Fram Strait suggest that eastern Fram Strait may represent a less favorable part of the bowhead whale overwintering area.